OPTIMALISASI KEMAMPUAN KODER DALAM IMPLEMENTASI REKAM MEDIS ELEKTRONIK DI RSI. IBNU SINA 'YARSI' BUKITTINGGI - Yastori Yastori; Nurul Fitri Khumaira; Hasna Mirda Amazan (Jurnal Abdimas Bina Bangsa, 2023)
Minister of Health Regulation Number 24 of 2022 concerning Medical Records gave birth to the latest regulations concerning digital technology, electronic systems and electronic signatures, obligations to administer Electronic Medical Records (RME) and ownership of Medical Records and confidentiality. This regulation aims to improve the quality of health services, provide legal certainty in the administration and management of medical records, guarantee the security, confidentiality, integrity and availability of medical record data and realize the implementation and management of medical records that are digital based and integrated. disease codification and appropriate medical action in health care facilities in preparing the ability to deal with RME. Coding accuracy is closely related to claims or hospital financing finances. Based on the preliminary study, there are pending claims, among others due to inaccuracies in coding or incompleteness, incompatibility of supporting document files or evidence in line with the diagnosis written on the medical record documents and the absence of optimal preparation for RME. This Community Service Activity was held on Tuesday, March 21, 2023 with the aim of providing socialization of understanding and knowledge related to optimizing coder capabilities in minimizing cases of pending claims and preparing RME. The dedication method is carried out in the form of lectures, outreach and discussion. The activity went smoothly, and it can be seen that the coder has begun to understand how to optimize the ability and understanding of the coder based on both coding regulations and regulations that apply with health insurance providers so as to minimize pending cases. It is recommended that in the future, training on pending claim cases with coders will be carried out to train understanding and improve coder skills in responding to the challenges of Electronic Medical Records